Virginia 1619 : slavery and freedom in the making of English America - Musselwhite, Paul; Mancall, Peter C.; Horn, James, 1953- (Omohundro Institute of Early American History and Culture ; The University of North Carolina Press, 2019)
This book provides an opportunity to reflect on the origins of English colonialism around the Chesapeake Bay and the Atlantic world. As the essays here demonstrate, Anglo-Americans have been simultaneously experimenting with representative government and struggling with the corrosive legacy of racial thinking for more than four centuries. Virginia, contrary to popular stereotypes, was not the product of thoughtless, greedy, or impatient English colonists. Instead, the emergence of stable English Atlantic colonies reflected the deliberate efforts of an array of actors to establish new societies based on their ideas about commonwealth, commerce, and colonialism. Looking back from 2019, we can understand that what happened on the shores of the Chesapeake four hundred years ago was no accident.